Detection of Alcohol Content in Food Products by Lossy Mode Resonance Technique. Issue 7 (1st July 2022) - Kavita,; Jyoti,; Mishra, S. K.; Mishra, A. K.; Misra, K. P.; Verma, R. K.
Abstract : The study deliberates the detection of ethanol/methanol concentration utilizing the phenomenon of lossy mode resonances on the multimode optical fiber by coating ZnO nanorods and bulk layers of TiO2 to serve as a lossy mode exciting layer. These layers have been characterized by FESEM, and their composition has been confirmed by EDS spectroscopy. Sensitivity of the ZnO nanorod coated optical fiber probe was found to be 28898.46 nm RIU −1, which is four times the sensitivity of the ZnO nanowire grown gas sensor for 1000 ppm of ethanol. Further, it is 4.5 times the sensitivity of TiO2 coated fiber probe. The sensitivity of TiO2 coated fiber optic probe comes about 7962.88 nm RIU −1, for methanol detection. The study reveals that the ZnO nanorod grown probe is highly recommended owning to the high figure of Merit i.e., 171.64 along with high sensitivity and detection accuracy values. The selectivity test also confirms the selectivity of this probe towards ethanol with ZnO NRs. Therefore, the development of an easy, durable, low-cost, and highly sensitive optical fiber sensing probe for the detection of ethanol and methanol has been achieved that may find ample considerations by the researchers in this field.